Designing mobile autonomous robots - Holland, John M. (Newnes, 2004)
Designing Autonomous Mobile Robots introduces the reader to the fundamental concepts of this complex field. The author addresses all the pertinent topics of the electronic hardware and software of mobile robot design, with particular emphasis on the more difficult problems of control, navigation, and sensor interfacing. Covering topics such as advanced sensor fusion, control systems for a wide array of application sensors and instrumentation, and fuzzy logic applications, this volume is essential reading for engineers undertaking robotics projects as well as undergraduate and graduate students studying robotic engineering, artificial intelligence, and cognitive science. Its state-of-the-art treatment of core concepts in mobile robotics helps and challenges readers in exploring new avenues in an exciting field. The accompanying CD-ROM provides software routines for the examples cited as well as an electronic version of the text. *Authored by a well-know pioneer of mobile robotics *Learn how to approach the design of and complex control system with confidence.